Well-defined imidotitanium alkyl cations: agostic interactions, migratory insertion vs.[2+2] cycloaddition, and the first structurally authenticated AlMe(3) adduct of any transition metal alkyl cation. - Bolton, P; Clot, E; Cowley, A; Mountford, P (2005)
The imidotitanium alkyl cations [Ti(NtBu)(Me3[9]aneN3)R]+ (R = Me (3+) or CH2SiMe3(4+)) possess either a very weak alpha-agostic or beta-Si-C agostic interactions, respectively, according to 13C and 29Si NMR and DFT studies; reaction of (4+) with iPrNCNiPr gives totally selective insertion into the Ti-alkyl bond; reaction of 3+ with AlMe3 gives the first structurally characterised AlMe3 adduct of a transition metal alkyl cation (Me3[9]aneN3 = 1,4,7-trimethyltriazacyclononane).